RVCL-S and CADASIL display distinct impaired vascular function. (4th September 2018) - de Boer, Irene; Stam, Anine H.; Buntinx, Linde; Zielman, Ronald; van der Steen, Iris; van den Maagdenberg, Arn M.J.M.; de Koning, Eelco J.P.; Ferrari, Michel D.; de Hoon, Jan N.; Terwindt, Gisela M.
Abstract : Objective: We aimed to evaluate the role of endothelial-dependent and endothelial-independent vascular reactivity in retinal vasculopathy with cerebral leukoencephalopathy and systemic manifestations (RVCL-S) and cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), both cerebral small vessel diseases are considered models for stroke, vascular dementia, and migraine. Methods: RVCL-S (n = 18) and CADASIL (n = 23) participants with TREX1 and NOTCH3 mutations, respectively, were compared with controls matched for age, body mass index, and sex (n = 26). Endothelial function was evaluated by flow-mediated vasodilatation, and endothelial-independent vascular reactivity (i.e., vascular smooth muscle cell function) was assessed by dermal blood flow response to capsaicin application. Results: Flow-mediated vasodilatation was decreased in participants with RVCL-S compared with controls (2.32% ± 3.83% vs 5.76% ± 3.07% change in diameter, p = 0.023) but normal in participants with CADASIL. Vascular smooth muscle cell function was reduced in participants with CADASIL compared with controls (maximal dermal blood flow increase at 40 minutes after capsaicin: 1.38 ± 0.88 vs 2.22 ± 1.20 arbitrary units, p = 0.010) but normal in participants with RVCL-S. Conclusions: We identified endothelial dysfunction in RVCL-S and confirmed impaired vascular smooth muscle cell relaxation in CADASIL. Our findings may prove to be biomarkers for disease progression in both monogenic cerebral small vessel diseases and improve mechanistic insight in their pathophysiology. This may help in understanding common neurovascular disorders, including stroke, dementia, and migraine.